Giant Ectopic Ureter Mimicking Pelvic Organ Prolapse: A Case Report - Adnan Simsir; Fuat Kizilay; Bilbasar Yildiz; Oktay Nazli (Case Reports in Urology)
Ectopic ureter is one of the most common urinary tract anomalies. We, herein, present a case of a giant ureter with ectopic orifice, mimicking pelvic organ prolapse, which is the first in the literature. A 59-year-old female patient presenting with frequently recurrent urinary tract infection had grade 3 pelvic organ prolapse. On examination, the organ producing the appearance of prolapse was found to be a right ureter of giant size and was obstructed by a large stone at the distal segment. The proximal end of the ureter ended blindly. After exploration, the stone was removed, the ureter was detached from the urethra, and the lumen was tied off and cut 5 cm proximally. At 6 months postoperatively, the patient is being followed up without any clinical problems. In such cases with nonfunctioning renal segment draining proximally, the chance of cure can be obtained without a need for a comprehensive intervention such as total abdominal ureterectomy.